Effect of severity of vestibular dysfunction on postural instability in idiopathic bilateral vestibulopathy. (May 2013) - Fujimoto, Chisato; Murofushi, Toshihisa; Chihara, Yasuhiro; Ushio, Munetaka; Suzuki, Mitsuya; Yamaguchi, Takuhiro; Yamasoba, Tatsuya; Iwasaki, Shinichi
Abstract Conclusions: Foam posturography reveals that idiopathic bilateral vestibulopathy (IBV) significantly affects postural stability. Instability was more severe in patients with damage to both of the vestibular nerve systems. Residual function in the spared vestibular nerve system might contribute to postural stability in IBV. Objective: Postural stability was assessed using foam posturography in patients with IBV according to whether the inferior, superior or both of the vestibular nerve systems were affected. Methods: Two-legged stance tasks were performed by patients with IBV (n = 29) in four conditions: eyes open with and without foam rubber, and eyes closed with and without foam rubber. We examined six variables: the velocity of movement of the center of pressure (COP), the envelopment area traced by the movement of the COP, Romberg's ratio of velocity and area, and the foam ratios of velocity and area. Results: The presence of IBV was significantly positively related to all the variables in adjusting for the subjects' gender and age (p < 0.001). Five of the 29 patients (17%) with IBV required assistance to prevent falling with eyes closed/foam rubber. Four of these five patients showed bilateral canal paresis in caloric testing and bilaterally no responses in cervical vestibular evoked myogenic potential testing.